1998
DOI: 10.1103/physrevb.57.r3185
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-drivensp3tosp2transformation in carbon nitride materials

Abstract: The coordination of carbon as a function of nitrogen concentration in energetically deposited carbon nitride films has been systematically studied. A structural transformation from primarily sp 3-bonded to sp 2-bonded carbon and a density decrease from 3.3 to 2.1 g/cm 3 were observed as the nitrogen concentration increases from 11 to 17 %. Calculations on nitrogen-substituted carbon clusters indicate that there is a preference to form sp 2-bonded carbon when the nitrogen concentration is larger than 12%. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(60 citation statements)
references
References 22 publications
(35 reference statements)
3
57
0
Order By: Relevance
“…This trend indicates that substantial amounts of nitrogen atoms are also etched by the incoming species. The liberated nitrogen atoms recombine to form N 2 molecules, which can either diffuse to the surface or stay inside the film inducing the formation of voids (low density) [7,13,14]. The ERDA and NRA measurements confirm these arguments and reveal a systematic presence of a significant amount of hydrogen and oxygen.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…This trend indicates that substantial amounts of nitrogen atoms are also etched by the incoming species. The liberated nitrogen atoms recombine to form N 2 molecules, which can either diffuse to the surface or stay inside the film inducing the formation of voids (low density) [7,13,14]. The ERDA and NRA measurements confirm these arguments and reveal a systematic presence of a significant amount of hydrogen and oxygen.…”
Section: Resultssupporting
confidence: 68%
“…The modes at 1400 and 1570 cm À1 are still debated [5,6,8]. The absorption band lying between 2000 and 2500 cm À1 suggests the presence of the chemical groups isonitrile and nitrile (triple bonded CN), which may terminate a chain and, thus, determines the extent of the void structure [7,14]. This result is confirmed by the band around 3400 cm À1 , associated with the OH vibration, suggesting a high atmospheric contamination by oxygen and water in good agreement with the ERDA and NRA results discussed above.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the disordered structure reduces the energy by relaxing some compressive stress, which eventually favor the formation of sp 2 bonds [60,61]. Jiang et al [62] described that above 12% nitrogen concentration more sp 2 carbon bonds are formed by preferential thermodynamic and kinetic reactions. Wang et al [61] pointed out that sp 2 bonded carbon atoms increases with increasing nitrogen partial pressure.…”
Section: Materials Characterization Resultsmentioning
confidence: 99%
“…Compared with pristine TiO 2 , TiO 2 /CM, and TiO 2 /CMB show the transitions of 1s → B* and 1s → σ * in both carbon K edge and nitrogen K edge. More importantly, the relative intensities of the two transitions (the 1s → B* transition peaks are very sharp and intense for TiO 2 /CM and TiO 2 /CMB) demonstrated that the outer layers of the TiO 2 /C 3 N 4 nanoparticles exclusively consisted of sp 2 hybridized carbon and nitrogen atoms, [16] which further proves the thin layers are composed of carbon nitride. Corresponding selected area electron diffraction patterns illustrates that the C 3 N 4 does not have obvious impact on the crystallinity of the TiO 2 nanoparticles ( Figure S4, Supporting Information).…”
mentioning
confidence: 84%